Restless leg syndrome in multiple sclerosis: a case–control study - Aljarallah, Salman; Alkhawajah, Nuha; Aldosari, Omar; Alhuqbani, Mohammed; Alqifari, Faisal; Alkhuwaitir, Bassam; Aldawood, Abdullah; Alshenawy, Omar; BaHammam, Ahmed S. (Frontiers in Neurology, 2023)
Objectives: This study assessed the prevalence of restless leg syndrome (RLS) among patients with multiple sclerosis (pwMS) and the association between RLS and MS disease duration, sleep disturbance, and daytime fatigue. Methods: In this cross-sectional study, we interviewed 123 patients via phone calls using preset questionnaires containing the International Restless Legs Syndrome Study Group (IRLSSG) diagnostic criteria, Pittsburgh Sleep Quality Index (PSQI), and Fatigue Severity Scale (FSS) diagnostic criteria validated in both Arabic and English. The prevalence of RLS in MS was compared to a group of healthy controls. Results: The prevalence of RLS in pwMS, defined by meeting all four requirements included in the IRLSSG diagnostic criteria, was 30.3% compared to 8.3% in the control group. About 27.3% had mild RLS, 36.4% presented with moderate, and the remaining had severe or very severe symptoms. Patients with MS who experience RLS had a 2.8 times higher risk of fatigue compared to pwMS without RLS. pwMS with RLS had worse sleep quality with a mean difference of 0.64 in the global PSQI score. Sleep disturbance and latency had the most significant impact on sleep quality. Conclusion: The prevalence of RLS among MS patients was significantly higher compared to the control group. We recommend educating neurologists and general physicians to increase their awareness of the increasing prevalence of RLS and its association with fatigue and sleep disturbance in patients with MS.